Overcoming diffusion limitations in supercapacitors using layered electrodes - Drummond, R; Huang, C; Grant, P; Duncan, S (Elsevier, 2019)
The impact of multi-layered electrode microstructures on the dynamic capacitance of electrochemical double layer supercapacitors is investigated. An electrochemical model that describes ion diffusion and double layer dynamics across the layered electrodes is first developed and then matched to experimental data. With TiO2 particulate and carbon nanotube layered electrodes, two knee frequencies were observed in the real and imaginary capacitance plots in both experiment and model simulations. These two knee frequencies resulted in an increase in real capacitance at high frequencies (ω ≈ 100 − 102 rad s−1) but a reduction at lower frequencies (ω ≈ 10−2 rad s−1), with the response being largely insensitive to the relative layer thicknesses. The increased capacity at high frequencies was due to increased ion mobility across the electrodes caused by the layering, allowing diffusion limitations of identical homogeneous electrodes to be overcome. These results imply the suitability of layered electrodes for applications with highly dynamic charge profiles and/or relatively thick electrodes.